Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus - Sommer, David; Hillert, Oliver; Hrůzová, Lucie; Král, David (Zootaxa, 2021)
Bolbelasmus (Bolbelasmus) zagrosensis Sommer, Hillert, Hrůzová & Král, new species, from Iran is described, illustrated and compared with its congeners known from the western Palaearctic region. An updated key to the western Palaearctic species of the nominotypical subgenus is provided. New country record of B. (B.) nireus (Reitter, 1895) from Greece (island of Rhodes) is reported. Distribution of B. (B.) makrisi Miessen, 2011, B. (B.) nireus and the new species is summarized and mapped.